2022
DOI: 10.21203/rs.3.rs-2289519/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and associated risk factors for Salmonella enterica contamination of cow milk and cottage cheese Ethiopia

Abstract: Animal sourced foods, such as dairy products, are common sources of Salmonella enterica, a foodborne pathogen of increasing global concern, particularly in developing countries. In Ethiopia, most data on the prevalence of Salmonella in dairy products is highly varied and limited to a specific region or district. Furthermore, there is no data available on the risk factors for Salmonella contamination of cow milk and cottage cheese in Ethiopia. This study was therefore conducted to determine the presence of Salm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 22 publications
(11 reference statements)
3
8
0
Order By: Relevance
“…In SNNP, during wet season the prevalence of Salmonella was higher in pasteurized milk 3% (n = 6) but not signi cantly higher compared to raw milk and cottage cheese as shown in (Table 1). Even though the pattern detection of Salmonella is higher in raw milk 29.2% (n = 7) and pasteurized milk 25% (n = 6) in the dry season compared to cottage cheese 8.3% (n = 1) doesn't have a signi cant variation (χ2 = 2.00, P = 0.367) as it was outlined in Bedassa et al, (2023). The pattern of Salmonella prevalence in the Amhara region revealed that it was highly detected in raw milk 20% (n = 4) than in pasteurized milk 15% (n = 3) during the wet season but no signi cant variation has observed (Table 1).…”
Section: Comparison Of Overall Prevalence Of Salmonella Between Dry A...mentioning
confidence: 78%
See 4 more Smart Citations
“…In SNNP, during wet season the prevalence of Salmonella was higher in pasteurized milk 3% (n = 6) but not signi cantly higher compared to raw milk and cottage cheese as shown in (Table 1). Even though the pattern detection of Salmonella is higher in raw milk 29.2% (n = 7) and pasteurized milk 25% (n = 6) in the dry season compared to cottage cheese 8.3% (n = 1) doesn't have a signi cant variation (χ2 = 2.00, P = 0.367) as it was outlined in Bedassa et al, (2023). The pattern of Salmonella prevalence in the Amhara region revealed that it was highly detected in raw milk 20% (n = 4) than in pasteurized milk 15% (n = 3) during the wet season but no signi cant variation has observed (Table 1).…”
Section: Comparison Of Overall Prevalence Of Salmonella Between Dry A...mentioning
confidence: 78%
“…2) value chains of the raw milk and processer 20% (n = 2) value chain of pasteurized milk during the wet season. The detection of Salmonella during dry season was highly detected in the producer 40% ( n = 4) value chain of raw milk and retailer 30% (n = 3) value chain of pasteurized even though no signi cant variation has been observed (χ2 = 2.7, P = 0.74) (Bedassa et al,2023).…”
Section: Comparison Of Overall Prevalence Of Salmonella Between Dry A...mentioning
confidence: 93%
See 3 more Smart Citations